VLOGSCAPE SHOWDOWN CHALLENGE: LEVERAGING TIKTOK AND PADLET TO ALLEVIATE SPEAKING ANXIETY AMONG POLITEKNIK MERSING ENGINEERING STUDENTS - Fairuz Umira Azmi; Tan Wei Xing; Mohd Izmafaimal Abdul Manaf; Melor Md Yunus (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The Vlogscape Showdown Challenge is an innovative web-based platform that engages students in video blogging, enhancing their creativity and storytelling skills. Utilizing Padlets for peer reviews and anonymous reflections, this innovation examines its impact on students’ ability to express ideas through video, while also addressing speaking anxiety. By fostering a supportive environment, the platform boosts self-expression and confidence in public speaking. Findings indicate that participation improves video blogging skills and significantly reduces speaking anxiety, promoting inclusive learning and personal development. Future research can further explore long-term studies to assess the sustained impact of the Vlogscape Showdown Challenge on speaking skills over an extended period.